2023
DOI: 10.1111/ans.18671
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for sigmoid volvulus managed with and without early definitive surgery: 20‐year experience in a tertiary referral centre

Shriranshini Satheakeerthy,
Priscilla Leow,
Benjamin Hall
et al.

Abstract: BackgroundSigmoid volvulus is rare in Western countries. Patients at risk of sigmoid volvulus are often older with significant co‐morbidity. Without sigmoid colectomy there is a high recurrence rate, but indications for surgery are controversial.MethodsA retrospective observational study was conducted by reviewing clinical records of patients admitted to Waikato Hospital 1 January 2000 to 1 January 2020 with a diagnosis of sigmoid volvulus. Patient characteristics, clinical features, investigations, management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In the patient group with acute cholecystitis, which is another risky surgery requirement and CCI determines the risk of preoperative mortality, complications were more common in those with CCI>6 [37]. Satheakeerthy et al found the median CCI score to be 4 in their study [38]. In the same study, they followed up 48% of the patients non-operatively and reported that recurrence developed in 63%.…”
Section: Discussionmentioning
confidence: 94%
“…In the patient group with acute cholecystitis, which is another risky surgery requirement and CCI determines the risk of preoperative mortality, complications were more common in those with CCI>6 [37]. Satheakeerthy et al found the median CCI score to be 4 in their study [38]. In the same study, they followed up 48% of the patients non-operatively and reported that recurrence developed in 63%.…”
Section: Discussionmentioning
confidence: 94%
“…
We read the article written by Satheakeerthy et al 1 on the acute and elective treatment of sigmoid volvulus (SV). Our comments relate to the details of SV management based on our 1071-case experience treated over 57-year period from June 1966 to July 2023, which series contains the most comprehensive single-centre SV data over the world.
…”
mentioning
confidence: 99%